2019
DOI: 10.3324/haematol.2019.223032
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of extramedullary acute myeloid leukemia detected by 18FDG-PET/CT: final results from the prospective PETAML trial

Abstract: IntroductionAcute myeloid leukemia (AML) may present with either concomitant or isolated extramedullary (EM) AML, also termed myeloid sarcoma (MS). EM AML is defined by infiltrating AML blasts effacing normal tissue as demonstrated by histological evaluation. 1 Data on the prevalence of EM AML are based on retrospective or clinical analyses, and they possibly under-estimate the true prevalence,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 21 publications
0
45
0
Order By: Relevance
“…In addition, for the right selection of therapeutic modalities, bone marrow biopsy should be performed to exclude medullary involvement [10,11]. Moreover, additionally performed Positron Emission Tomography and Computer Tomography allows for the evaluation of treatment response, reveals previously unnoticed manifestations, and increases diagnostic accuracy [12].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, for the right selection of therapeutic modalities, bone marrow biopsy should be performed to exclude medullary involvement [10,11]. Moreover, additionally performed Positron Emission Tomography and Computer Tomography allows for the evaluation of treatment response, reveals previously unnoticed manifestations, and increases diagnostic accuracy [12].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, PET-CT was reported to be useful as a diagnostic tool for extramedullary disease in patients with leukemia. In a recent prospective study, PET-CT had 77% sensitivity and 97% speci city for detecting extramedullary disease in AML patients [14]. In the present study, although the correlation between the SUVmax response and recurrence was di cult to analyze due to the lack of recurrence cases and the number of samples, we analyzed the factors affecting the recurrence and PMD showing treatment failure.…”
Section: Discussionmentioning
confidence: 89%
“…Several papers reported that PET/CT incidentally detected acute lymphoblastic leukemia (ALL) (8)(9)(10)(11), and a few studies have reported the evaluation and predictive value of PET/CT in patients with leukemia (12,13). The prospective PETAML trial reported that the specificity of 18 F-FDG-PET/CT for diagnosis of extramedullary acute myeloid leukemia was 97%, despite hematological remission (14). In a retrospective study of 28 children suspected of leukemia progression or recurrence during / after chemotherapy or allo-HSCT, 14 cases with positive 18 F-FDG-PET/CT scans were associated with increased blasts in bone marrow biopsies, and the mean SUV max was significantly higher than what is seen with infectious diseases (15).…”
Section: Discussionmentioning
confidence: 99%